2003
DOI: 10.1093/jn/133.11.3950s
|View full text |Cite
|
Sign up to set email alerts
|

School Snacks Containing Animal Source Foods Improve Dietary Quality for Children in Rural Kenya

Abstract: Provision of a snack at school could help alleviate the micronutrient malnutrition that is common among schoolchildren in developing countries. The Child Nutrition Project was designed to compare the efficacy of three school snacks in improving growth and cognitive function of children in rural Kenya. The snacks provided approximately 20% of the children's energy requirement, and were composed of equicaloric portions of githeri (a vegetable stew) alone (Energy group), githeri plus milk (Milk group) or githeri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 13 publications
5
111
0
2
Order By: Relevance
“…A Cochrane review on school feeding (Kristjansson and others 2009) conducted a meta-analysis of three randomized controlled trials in three LMICs: Jamaica (Powell and others 1998), Kenya (Grillenberger and others 2003), and China (Du and others 2004). The meta-analysis found a small yet significant effect on weight (0.39 kilogram, 95 percent confidence interval 0.11, 0.67) and a small nonsignificant effect on height gain (0.38 centimeters, 95 percent confidence interval -0.32, 1.08).…”
Section: Anthropometry and Nutritionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Cochrane review on school feeding (Kristjansson and others 2009) conducted a meta-analysis of three randomized controlled trials in three LMICs: Jamaica (Powell and others 1998), Kenya (Grillenberger and others 2003), and China (Du and others 2004). The meta-analysis found a small yet significant effect on weight (0.39 kilogram, 95 percent confidence interval 0.11, 0.67) and a small nonsignificant effect on height gain (0.38 centimeters, 95 percent confidence interval -0.32, 1.08).…”
Section: Anthropometry and Nutritionmentioning
confidence: 99%
“…In the Jamaica study, 395 children in grades 2-5 were given breakfast for a year (Powell and others 1998). In Kenya, grade 1 schoolchildren were given meat, milk, or an energy supplement for 18 months (Grillenberger and others 2003). In China, the study focused on girls age 10 years who received milk supplementation (Du and others 2004).…”
Section: Anthropometry and Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient intakes and probability of nutrient adequacy Nutrient intakes were calculated for each individual schoolchild, for each day, using an international food composition table adapted for use in the CNP study (16,17) . The database contains complete nutrient values for the foods commonly consumed in rural Kenya.…”
Section: Food Intakementioning
confidence: 99%
“…19 compensatory reduction in food intake at other times A few studies documented a compensatory adjustment in appetite (supplemented children ate less at the next meal). 8 24 Four studies in which the benefit of supplements was less than expected were done in very poor areas in Peru, 20 Jamaica, 23 Kenya, 22 and India. 12 The authors of two of these studies concluded that children who had been given a substantial supplement at school were provided with less food at home (substitution).…”
Section: Bioavailabilitymentioning
confidence: 99%